2018
DOI: 10.1177/2041419618789438
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability analysis of tunnel linings under blast loading

Abstract: In the present study, a comparative assessment on the performance of conventional and advanced tunnel lining materials subjected to blast loading is done using a three-dimensional non-linear finite element analysis procedure. The conventional tunnel lining materials analyzed herein are plain concrete, steel, reinforced cement concrete, and steel fiber-reinforced concrete. The advanced tunnel lining materials analyzed herein are dytherm, polyurethane, and aluminum syntactic foam sandwich panels with steel-foam-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 25 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Also, it was observed that the lining portion located near to the blast source experienced a considerable amount of permanent deformation. Chaudhary et al [44] presented a comparison between the use of conventional and advanced tunnel lining materials subjected to blast loading of 10 kg TNT. The plain concrete (PC), steel reinforced cement concrete and steel fiber reinforced concrete(SFRC) were considered as conventional materials, see Fig.…”
Section: Influence Of Lining Materials In Tunnelmentioning
confidence: 99%
“…Also, it was observed that the lining portion located near to the blast source experienced a considerable amount of permanent deformation. Chaudhary et al [44] presented a comparison between the use of conventional and advanced tunnel lining materials subjected to blast loading of 10 kg TNT. The plain concrete (PC), steel reinforced cement concrete and steel fiber reinforced concrete(SFRC) were considered as conventional materials, see Fig.…”
Section: Influence Of Lining Materials In Tunnelmentioning
confidence: 99%
“…Tunnels are considered as high‐risk zones due to the presence of numerous patronage in confined space at a single location 5 . Some of the manmade hazards in the tunnels that have caused severe loss of life and property are Bayrampasa metro tunnel attack, London underground metro attack, Moscow metro tunnel attack, Minsk metro bombing, and Saint Petersburg metro attack 6 . Therefore, the blast resistant design of tunnels and other underground utility structures is required.…”
Section: Introductionmentioning
confidence: 99%
“…Later, London underground metro tunnels had experienced three explosion events where 700 people were injured and 52 deaths were reported [2]. In past two decades, there has been a rise in blastrelated disasters at Moscow metro tunnel (2010), Minsk metro (2011), Bayrampasa metro (2015), Saint Petersburg metro (2017) and many more [3]. Due to several uprising and insurgency in the world, tunnels have faced extreme loading events in the past few decades [3].…”
Section: Introductionmentioning
confidence: 99%
“…In past two decades, there has been a rise in blastrelated disasters at Moscow metro tunnel (2010), Minsk metro (2011), Bayrampasa metro (2015), Saint Petersburg metro (2017) and many more [3]. Due to several uprising and insurgency in the world, tunnels have faced extreme loading events in the past few decades [3]. Therefore, blast resistant design of tunnel is necessary to prevent the casualties and strengthen the metro tunnel against blast-related disasters.…”
Section: Introductionmentioning
confidence: 99%